Development of anti-cancer drugs for tumor-associated macrophages: a comprehensive review and mechanistic insights - Bai, Bingjun; Xie, Shangzhi; Wang, Ya; Wu, Fei; Chen, Yao; Bian, Jia; Gao, Xing (Frontiers in Molecular Biosciences, 2024)
This review provides an in-depth summary of the development of anti-cancer drugs for tumor-associated macrophages (TAMs), with a particular focus on the development and tissue specialization of macrophages, and factors influencing the polarization of M1 and M2 macrophages, and mechanistic insights underlying the targeting therapeutic approaches. TAMs, pivotal in the tumor microenvironment, exhibit notable plasticity and diverse functional roles. Influenced by the complex milieu, TAMs polarize into M1-type, which suppresses tumors, and M2-type, which promotes metastasis. Notably, targeting M2-TAMs is a promising strategy for tumor therapy. By emphasizing the importance of macrophages as a therapeutic target of anti-cancer drugs, this review aims to provide valuable insights and research directions for clinicians and researchers.